Comparative Study of Artificial Kidneys for Implantation - nayef, Ali Mohammed; Saleh, Ibrahim Mohammed Ali; Alwan, Aseel Wasfy; Abd_aljaleel, Manar Abd_alghany (American Journal of Botany and Bioengineering, 2025)
Chronic kidney disease (CKD) and end-stage renal disease (ESRD) affect millions globally, yet the availability of transplantable organs remains insufficient to meet patient needs. Despite decades of reliance on dialysis, limitations in quality of life, mobility, and survival rates underscore a critical gap in renal replacement therapies. This study presents a comparative evaluation of current and emerging artificial kidney technologies, particularly focusing on bioartificial and implantable systems such as iRAD and wearable dialysis devices. Through a multidisciplinary review encompassing engineering design, biocompatibility, patient outcomes, and cost-effectiveness, the research assesses clinical readiness and future potential of these innovations. The analysis reveals that while promising advances have been made—especially in tissue-driven and silicon-based designs—significant challenges remain in achieving long-term biocompatibility, autonomous function, and regulatory approval. The findings highlight the importance of standardized evaluation protocols and interdisciplinary collaboration to realize fully implantable bioartificial kidneys as viable alternatives to transplantation.